PALLADIUM SOLUBILITY IN WATER-BEARING SILICATE MELTS: EVIDENCE FROM EXPERIMENTAL DATA - Bezmen N.I.; Gorbachev P.N.; Azif E.; Naldrett A.J. (My University, 2006)
One of the most interesting geological problems, bearing both theoretical and practical significance, is the study of PGE geochemistry in the formation of the Earth’s crust and mantle and in differentiated maficultramafic magmatic complexes, as well as in related PGM mineralization. An important part of this problem is the experimental study of PGE solubility in natural and model silicate melts depending on oxygen fugacity—the main parameter of redox conditions of the magmatic process.